O uso dos recursos de commodities para o financiamento da defesa por países da América do Sul: possibilidades para o Brasil - Ramalho, Horácio de Sousa (2020)
The present work seeks to address in an exploratory and qualitative way, the use of commodity resources by countries in South America to finance defense and the possibilities for Brazil. This is a way that several countries rich in natural resources use to complement their defense budget and thus make purchases of military equipment. This research is important for addressing the budgetary needs of the Brazilian defense sector. This is because countries with smaller economies and defense budgets in the region were able to carry out a considerable refit in the period from 2000 to 2019. This situation could be realized because some countries in the region were able to supplement the budget of their military forces with resources from export earnings. of commodities. This work seeks to explain from a qualitative analysis and under a comparative analysis, how countries in the region, in particular Chile and Venezuela, were able to expand their military capabilities, with an emphasis on equipment, based on an off-budget model backed by commodity resources, respectively copper and oil. To this end, this work is supported by the literature on the Brazilian defense budget and its structure, off-budget financing mechanisms, specifically those in Chile and Venezuela, focused on commodities and their legal aspects and operational problems. In order to advance the possibilities for Brazil, Santos (2019) 's work on a Constitutional Defense Financing Fund (FCF Def) for the exploitation of iron ore and its operation will be based on theoretical support. Complementing the previous literature, a contribution of this work, by transforming the FCF Def profile into a multimarket fund that would adopt what in this piece we call the 'individual contract approach', with a view to providing the Ministry of Defense of Brazil with a alternative financing model. The data will come from the Ministry of Defense's 'Citizen Information Service' (SIC / MD), contacted through the Access to Information website (FalaBr), from the Transparency Portal, as well as from specialized literature, including those contained in the publication The Military Balance, from the International Institute for Strategic Studies (IISS), in material published by the Stockholm International Peace Research Institute (SIPRI) and in the Arms Transfers Database, also from SIPRI. These sources will be for the knowledge about the Chilean and Venezuelan models of acquisition and the state of its armed forces. It is concluded that the possibility for Brazil to implement a similar system is viable, since the country has material conditions and a legal and theoretical framework that allows such an undertaking, leaving only the political variable, that is, the will of the government for this action.